Numerical Study of a Water Gas Shift Fixed Bed Reactor Operating at Low Pressures - Wail El-Bazi; Mustapha Bideq; Abderrahim El-Abidi; Said Yadir; Bajil Ouartassi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Today, hydrogen has become one of the most promising clean energy. Several processes allow obtaining hydrogen, among them there is the Water Gas Shift (WGS) reaction. On an industrial scale, WGS reaction takes place at high pressure [25–35 bar]. At high pressure, the cost of the process rises due to the energy consumed by compression, and the reduction in the lifetime of the equipment and the catalyst. At low pressures, catalyst lifetime can reach many years and the energy cost is reduced. It is for this reason that we are interested in modelling and simulation of a WGS converter operating at low pressures close to atmospheric pressure. In this work, a numerical study was conducted in order to determine the conditions allowing good rector operating at low pressure. A number of drawbacks of the process were identified. These drawbacks are essentially the non-negligible pressure drops and the strong intraparticle diffusion resistances. The prediction of the concentrations and the reaction rate within the pellet showed that the active zone of the pellet is located near the particle surface. It has also been shown that the resistances to interfacial mass and heat transfer are insignificant. The study of pressure effect showed that the pressure increase reduces the required catalyst mass to achieve equilibrium. Finally, this work revealed that the decrease in temperature and the increase in the concentrations of the reactants by increasing their fluxes, make it possible to increase the effectiveness factor of the catalyst and the conversion of carbon monoxide. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).